Locking Down the South Bronx - Susan Belford (Integral Review, 2010)
In this brief analysis is the intended beginning of a systemic integral analysis of the social systems and structures in use in the South Bronx, New York City. Informed by the writing of Jonathan Kozol as well as current articles in the New York Times, this analysis uses the systems theories of Talcott Parsons and Donella Meadows and the human identity work of Vern Redekop to understand the exterior and interior dimensions of systemic oppression as experienced by residents of the South Bronx.